2022
DOI: 10.3390/molecules27154938
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Essential Trace and Toxic Elements Associated with Production and Manufacturing Processes in Galician Cheese

Abstract: The objective of this study was to determine the trace element composition and the toxic metal residues in Galician cow’s milk cheese produced in different systems (artisan, industrial, and organic). Fourteen elements (As, Cd, Co, Cr, Cu, Fe, Hg, I, Mn, Mo, Ni, Pb, Se, and Zn) were determined in 58 representative samples of Galician cheeses by inductively coupled plasma mass spectrometry. The toxic elements were present at low concentrations, similar to those reported for other unpolluted geographical areas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In delactosed mozzarella samples from Italy [ 26 ], an average value of 0.002 mg/kg was measured for As. Higher level of As in Galician cheese was detected only in cheeses made from cow milk from polluted regions [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In delactosed mozzarella samples from Italy [ 26 ], an average value of 0.002 mg/kg was measured for As. Higher level of As in Galician cheese was detected only in cheeses made from cow milk from polluted regions [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, in study of Crupi et al [ 26 ] regarding the consumption of delactosed mozzarella, any safety risk due to exposures to toxic elements was excluded. Galician cheeses were found to have a low level of toxic metal residues [ 27 ]. Generally, mineral elements ingested through the diet play an important role in the human body, and most biochemical reactions depend on or are influenced by these electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of elements in foods can be affected by various factors, including climate and translocation from soil, water, and air [ 19 ]. Research has shown that elemental fingerprints of dairy products can be used to discriminate their geographical origin [ 23 , 24 , 25 ], verify their PDO authenticity [ 20 , 26 , 27 , 28 , 29 ], identify breeding methods [ 30 ], assess production processes [ 31 ], and trace the production chain [ 32 ]. Accurate sampling is necessary to achieve these goals and encompass all variables that can influence the elemental fingerprint.…”
Section: Introductionmentioning
confidence: 99%